Identifying Students’ English Language Needs: Digital Business Students' Perspectives - Romadhon, Romadhon (Universitas Nurul Jadid, 2023)
This study examined the English language needs of students studying digital business, aiming to clarify their difficulties and provide recommendations for educators and policymakers. English is essential for communication between multinational corporations, start-ups, and freelancers in the digital business sector, making collaboration, communication, and information sharing easier. Students from various linguistic backgrounds may struggle to assimilate to English language requirements for their academic and professional tasks. The lack of knowledge on the specific English language requirements of students studying digital business was the cause of the current research gap. This study reveals that digital business students prioritize speaking skills, particularly in phone conversations and meeting discussions, as they are crucial for real-time interactions in the digital business environment. Writing skills are deemed less important, with 15% deemed very important. This suggests a shift towards skills better suited for immediate, interpersonal exchanges. The students also rank the functions of English language proficiency most frequently employed in their daily tasks, such as answering meeting questions, participating in discussions, speaking to foreigners by phone, answering working interview questions, scheduling appointments, writing CVs and application letters, writing reports, and responding to emails. The most prominent issues identified were presenting project/term papers orally, executing simulation tasks, attending group talks, and accurately speaking words. Listening skills were also identified as significant, with 55% of respondents stating their difficulty in capturing lecture notes via listening. Reading and analytical skills were identified as the most challenging, with 55% identifying key parts in texts and 35% predicting new vocabulary interpretations from context. Writing skills were identified as the most challenging, with 40% stating their difficulty. These findings emphasized the need for tailored approaches to enhance academic success and prepare students for the dynamic communication demands of the digital business world.